TWSME of a NiTi strip in free bending conditions: experimental and theoretical approach - A. Fortini; M. Merlin; R. Rizzoni; S. Marfia (Fracture and Structural Integrity)
This paper deals with the two-way shape memory effect (TWSME) induced on a strip of a nearequiatomic NiTi alloy by means of the shape memory cycling training method. This procedure is based on the deformation in martensite state to reach the desired cold shape followed by cycling the temperature from above Af to below Mf. To this end, the sample was thermally treated to memorise a bent shape, thermomechanical trained as described and thermally cycled in unloaded conditions in order to study the stability of the induced TWSME. Heating to Af was reached by a hot air stream flow whereas cooling to Mf was achieved through natural convection. The evolution of the curvature with the increasing number of cycles was evaluated. The thermomechanical behaviour of the strip undergoing uniform bending was simulated using a one-dimensional phenomenological model based on stress and the temperature as external control variables. Both martensite and austenite volume fractions were chosen as internal parameters and kinetic laws were used in order to describe their evolution during phase transformations. The experimental findings are compared with the model simulation and a numerical prediction based on the approach proposed in [25].